The accuracy of femoral component rotational measurements using computed tomography—a cadaveric study - Onyedikachi Eseonu; Calum Cree; Martin Sambrook; Mark Blyth; Bryn Jones (Arthroplasty, 2020)
Abstract Background CT scans can be used to assess the rotational alignment of the femoral component following total knee arthroplasty (TKA). This is done by calculating the posterior condylar angle (PCA). However, the methods used may not account for the biomechanical functionality of the TKA components. This cadaveric study aimed to determine whether the axis of scanning (mechanical or anatomical) alters the results of PCA calculations. Methods CT scans of 12 cadaveric adult femora were performed along the anatomical axis and the mechanical axis. The PCA was determined on each CT scan by measuring the relationship of the prosthetic posterior condyles to the surgical epicondylar axis of the femur. The mechanical and anatomical axis groups were further subdivided into best-fit and multi-slice subgroups. As a control, the posterior condylar angle was also calculated on photographic images of each femur. Bland-Altman plots were used to determine the correlation between the PCA values obtained from the different scanning axes and measurement techniques. Results There was no significant difference between the PCA measurements derived from anatomical and mechanical axis CT scans. The Pearson correlation co-efficient also indicated good correlation between the two scanning axes. Conclusion The axis of scanning does not significantly affect the PCA measurements. Therefore, the measurements may be reliably used for clinical decision-making, regardless of the axis of CT scanning.